MANAGEMENT OF QUADRIPLEGIA INDUCED BY SPINAL CORD INJURY WITH PANCHAKARMA - A CASE STUDY - Jain, Anup; Arun, Gupta; Ashok, Kumar (International Journal of Ayurveda and Pharma Research, 2016)
A 30 year old male patient with quadriplegia induced by spinal cord injury was treated with ayurvedic medicine and Panchkarma therapies. Patient presented with quadriplegia and inability to sit/stand even with support and having no bladder/bowel control. Spinal Cord Independence Measure (SCIM) was 16 showing high dependence and also muscle wasting was present. Patient had history of swimming pool accident causing fracture C4-C5 spine and fixation through surgery in 2011. Ayurveda explains this disease as Vatavyadhi. Snehana and Svedana formed the first line of treatment to pacify the vitiated Vata while Shalishashtikapindasveda and Matravasti worked as Balya for Mansa and Asthi dhatu and also Anulomana. Snehadhara improves motor and sensory system resulting in improved function of all limbs. Management was done with repeated admissions for Panchakarma therapy during which overall strength and reflexes improved with Spinal Cord Independence Measure (SCIM) score reaching 47 from original 16 indicating improvement in independence of patient from complete dependence to partial independence in six months time.